Methadone for Analgesia in Children with Life-Limiting Illness: Experience from a Tertiary Children's Health Service - Christine Mott; Amrita Sarpal; Krista Moss; Anthony Herbert (MDPI AG, 2018)
Methadone has the potential to assist in the management of pain in children with life-limiting illness, but its use is limited by its complex pharmacokinetic profile and limited research on its use in children. This is a retrospective review of the use of methadone as an analgesic in 16 children with life-limiting illness. Efficacy, dosing and side effect profile were analysed. Fifteen (94%) patients had improvements in their analgesia with minimal observed adverse effects. Patients were either rapidly converted from a prior opioid in one change or received methadone as an adjunct medication. Conversions were calculated using ratios frequently in the range of 10:1 to 20:1 from the oral morphine equivalent total daily dose (MEDD). Adjunct initial dosing was a low dose trial, often beginning with 1 mg at night. Only two patients required a dose adjustment due to side effects attributed to methadone. This was despite the cohort having significant underlying illnesses, extensive concurrent medications, and high methadone dosing where needed. Analysis of dosing and ratios indicates that an individualised approach is required. Based on this and on the infrequency of methadone use in this population, specialist assistance with dosing is recommended. Further research, including prospective and pharmacokinetic studies, is recommended.